2012
DOI: 10.1186/1756-0500-5-590
|View full text |Cite
|
Sign up to set email alerts
|

Age trends in the prevalence of cervical squamous intraepithelial lesions among HIV-positive women in Cameroon: a cross-sectional study

Abstract: BackgroundCervical squamous intra-epithelial lesions (SIL) are more frequent in HIV-positive women overall. However the appropriate age at which to begin and end cervical cancer screening for early detection of lesions in HIV-positive women is not clear. We assessed the age-specific prevalence of any SIL and SIL requiring colposcopy in HIV-positive women in Cameroon.MethodsWe enrolled, interviewed and conducted conventional cervical cytology in 282 women, aged 19–68 years, initiating antiretroviral therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
4
8
2
Order By: Relevance
“…This finding was also demonstrated in other studies . A study in Cameroon (Africa) showed that severe and less severe lesions among WLHIV were prevalent at all ages and that, therefore, an age‐targeted screening among those women are of little utility . The abnormal cervical cytology was present in 8.9% of women, whereas the HPV prevalence was 28.4%, similar data were found in another sites .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding was also demonstrated in other studies . A study in Cameroon (Africa) showed that severe and less severe lesions among WLHIV were prevalent at all ages and that, therefore, an age‐targeted screening among those women are of little utility . The abnormal cervical cytology was present in 8.9% of women, whereas the HPV prevalence was 28.4%, similar data were found in another sites .…”
Section: Discussionsupporting
confidence: 85%
“…showed that severe and less severe lesions among WLHIV were prevalent at all ages and that, therefore, an age-targeted screening among those women are of little utility. 26 The abnormal cervical cytology was present in 8.9% of women, whereas the HPV prevalence was 28.4%, similar data were found in another sites. 19,22 The performance of molecular biology screening can help to recognize the target population who needs to be attended more carefully, in low and middle development countries.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Initially, efforts to implement cytology-based screening in low income countries have been conducted since the early 1980s but they have failed to reduce the mortality rates. Amongst other factors [4]- [6], this failure can be attributed to limited knowledge and wrong perceptions of the risk factors of cervical cancer [1].…”
Section: Introductionmentioning
confidence: 99%
“…De Lemos and colleagues observed 12.1% abnormal cytology not otherwise specified (NOS) in 125 HIV-infected cases versus 5.4% in 112 controls ( = 0.05) [32]. A study of 276 unscreened HIV-infected women reported a 17.8% prevalence of SIL NOS [33]. Dames and colleagues found 44% of cervical abnormalities NOS after Pap/HPV screening of 100 HIVpositive women [2].…”
Section: Discussionmentioning
confidence: 99%